Ways of Developing Investment Activity in Commercial Banks - qizi, Mirkhaydarova Mokhira Mirakbar (European Journal of Life Safety and Stability (2660-9630), 2022)
The article analyzes the role of commercial banks in financing investment projects. The experience of developed foreign countries in financing investment projects is studied. The activities of commercial banks for lending to investment projects were studied and suggestions were made for their improvement.